EARLY OUTCOMES OF WILMS TUMOR SURGERY IN CHILDREN TREATED WITH PRE-OPERATIVE CHEMOTHERAPY: AN EXPERIENCE FROM CANCER DEDICATED CENTER - Ali, Sajid; Javed, Talha; Salim, Areej Muhammad; Latif, Tariq; Sheikh, Muhammad Ali (Journal of Ayub Medical College Abbottabad, 2025)
Background: In recent times’ advances in surgical technique and chemotherapy resulted survival rate in Wilms tumour patients approaching 90%. Therefore, the study aimed to assess the efficacy of preoperative chemotherapy and to document the early postoperative surgical and oncological outcomes. Methods: The patients with Wilms tumour were reviewed who underwent radical nephrectomy from April 2020 to May 2023. Factors related to demographics, radiological findings, treatment provided, response to chemotherapy, and short-term outcomes were assessed. Mean and standard deviations were used to describe categorical data while frequencies and proportions were used to describe quantitative data. Results: Ninety patients with Wilms tumour received pre-operative chemotherapy and underwent radical nephrectomy with a mean age of 3.35±2.20 years. The majority of the patients presented within three months of the onset of the symptoms (81.0%) and the common symptom was abdominal mass (77.7%). Most of the patients were lying in the intermediate-risk stratification group (70.0%). The mean operative time was 2.02±0.75 hours. The mean high dependency unit (HDU) stay was 1.57±1.31 days and the mean hospital stay was 3.47±1.14 days. Furthermore, surgical complications were reported in nine (10%) patient, and four patients had early relapse, and two expired. There was a statistically significant chemotherapy response in terms of tumour size (pre-chemotherapy 9.6±3.29 cm versus post-chemotherapy tumour size 7.1±2.8 cm). Conclusions: Despite the delayed presentation and large volume of tumours, the initial results are favourable. Additionally, preoperative chemotherapy has played a crucial role in reducing tumour size and enabling successful surgical removal.